The digesta passage rate among dairy cows with different abilities to consume large quantities of roughage : its impact on the milk production, and the reliability of the chemical fibre marker - Eklund, Maria Elisabeth (SLU/Dept. of Animal Nutrition and Management (until 231231), 2020)
The objectives of the present master thesis were to investigate the passage rate among lactating Holstein and Swedish red dairy cows to investigate the hypotheses of: 1) The cows’ individual total mean retention time (TMRT) has a negative relationship to the cows’ individual forage intake capacity. 2) A reduced TMRT contributes to a reduced feed efficiency, but a higher milk yield. 3) The chromium (Cr) mordanted fibre marker used in the present study is a reliable substitute for rumen evacuations when measuring TMRT for the solid digesta fraction. The study was divided into two parts, one marker method study, and one evaluation study. The marker method study was performed on 30 cows in mid lactation. The cows had free access of forage and a concentrate treatment of either 5.25 kg DM/day (5kgC) or 10.5 kg DM/day (10 kgC). The study was performed in four different study sessions of one week each, where each cow was included in one session only. A pulse dose of orally administered marker of 2 or 4 g of chromium (Cr) to measure the TMRT of the solid digesta fraction (TMRTCr), and 10 g of cobalt- ethylenediaminetetraacetic acid, to measure the TMRT of the liquid digesta fraction (TMRTCo), was given to each cow at h=0. This was followed by a scheduled faecal sampling session during a 164-hour period where a total of 24 faecal samples were collected from each cow. After completion of the four study sessions, 16 randomly chosen cows were selected for further analysis. The faecal samples got freeze dried, milled and analysed for Cr and cobalt (Co) concentrations. A plot of the marker concentrations was made for each cow and marker. A two-compartment, and age-independent model (G1G1) was thereafter used to make a curve fit and to predict TMRTCr and TMRTCo for each cow. Statistical analyses were performed by using SAS 9.4 MIXED procedure, proc REG and proc CORR. Statistical analyses was only performed on TMRTCr since the TMRTCo data turned out being unreliable. The Cr mordanted fibre marker was evaluated in a separate study session of ruminal evacuations per-formed on four ruminally fistulated Swedish red cattle. Indigestible neutral detergent fibre (iNDF) was used as an internal marker. Three ruminal evacuations were performed on all cows at different days and different times to compensate for diurnal variation in rumen iNDF-pool. Feeds and rumen contents were analysed for iNDF whereafter daily iNDF intake and rumen iNDF-pool was calculated. The intake-based TMRT (TMRTin) was thereafter calculated and compared to TMRTCr data which was achieved by a separate marker method session for the ruminally fistulated cows. Proc REG and proc CORR was used to analyse the data. A positive and significant relationship was shown considering feed efficiency and TMRTCr (P<0.05; R2=0.56), but no significant relationship was observed between TMRTCr and kg milk (P=0.87; R2=0.00), and neither between TMRTCr and kg energy corrected milk (P=0.22; R2=0.18). There was no positive relationship between the cows’ individual TMRTCr and forage DMI intake. The evaluation study could neither verify the Cr mordanted fibre marker as a reliable method to measure TMRT of the solid digesta phase. There was no significant relationship between TMRTCr and TMRTin (P=0.16, R2=0.71). TMRTCr was shown to underestimate the passage rate compared to the rumen evacuation method, which is different compared to other studies regarding this subject. Further research to evaluate the marker method is needed to get a better understanding of the reliability of this less invasive method. Further studies are also requested to further investigate the TMRT’s relation to milk production and feed effi-ciency among cows with different abilities to consume large quantities of roughage. Keywords: chemical markers, chromium, chromium mordanted fibre, cobalt, concentrate level, EDTA, eth-ylenediaminetetraacetic acid, forage consumption, iNDF, indigestible neutral detergent fibre, liquid digesta phase, mean retention time, MRT, rumen evacuation, solid digesta phase, TMRT, total mean retention time.